Effect of Cyclic Stretch on Neuron Reorientation and Axon Outgrowth - Lin, Ji; Li, Xiaokeng; Yin, Jun; Qian, Jin (Frontiers in Bioengineering and Biotechnology, 2020)
The directional alignment and outgrowth of neurons is a critical step of nerve regeneration and functional recovery of nerve systems, where neurons are exposed to a complex mechanical environment with subcellular structures such as stress fibers and focal adhesions acting as the key mechanical transducer. In this paper, we investigate the effects of cyclic stretch on neuron reorientation and axon outgrowth with a feasible stretching device that controls stretching amplitude and frequency. Statistical results indicate an evident frequency- and amplitude-dependence of neuron reorientation. That is, neurons tend to align away from stretching direction when stretching amplitude and frequency are large enough. On the other hand, axon elongation under cyclic stretch is very close to the reference case where neurons are not stretched. A mechanochemical framework is proposed by connecting the evolution of cellular configuration to the microscopic dynamics of subcellular structures, including stress fiber, focal adhesion and microtubule, yielding theoretical predictions that are consistent with the experimental observations. The theoretical work provides an explanation of neuron’s mechanical response to cyclic stretch, suggesting that the contraction force generated by stress fiber plays an essential role in both neuron reorientation and axon elongation. This combined experimental and theoretical study on stretch-induced neuron reorientation may have potential applications in neurodevelopment and neuron regeneration.